Frequency of Non-ST Segment Elevation Myocardial Infarction (NSTEMI) in Acute Coronary Syndrome With Normal Electrocardiogram (ECG): Insights From a Cardiology Hospital in Pakistan - Khan, Rozi (Cureus, 2020)
Introduction Patients presenting to the emergency department with a non-ST segment elevation myocardial infarction (NSTEMI) frequently have unremarkable electrocardiography (ECG) reports, alluding to the unreliable nature of ECG in diagnosing NSTEMI. This study aims to assess the burden of NSTEMI in acute coronary syndrome (ACS) with unremarkable ECG, elucidating that in patients presenting with acute retrosternal chest pain, NSTEMI should not be excluded unless cardiac enzyme levels are assessed. Methods All patients who fulfilled the inclusion criteria in the Department of Cardiology, Tabba Heart Institute, Karachi were included. After obtaining informed written consent, a detailed history was taken. Clinical examination was consequently performed, and an ECG, along with the cardiac enzymes implicated in ACS, such as troponin I, was evaluated. The proportion of normal ECGs in the context of an NSTEMI was duly noted. Result A total of 215 patients with ACS presenting within 24 hours of the onset of symptoms, on a background of unremarkable ECG reports, were included. One hundred thirty-eight (64.2%) were males and 77 (35.8%) were females, with the mean age being 54.3 + 7.6 years. A confirmed diagnosis of NSTEMI was made in 49 (22.8%) of the total cases. Conclusion The frequency of patients presenting with an NSTEMI within 24 hours of the onset of symptoms, and having normal ECG findings, was strikingly high in patients presenting to the Tabba Heart Institute, Karachi, Pakistan. These findings were more common in males and in older patients.